Who are American evangelical Protestants and why do they matter for US climate policy?. (30th November 2020) - Veldman, Robin G.; Wald, Dara M.; Mills, Sarah B.; Peterson, David A. M.
Abstract: White evangelical Protestants are the most skeptical major religious group in the United States regarding climate change. While their position of political influence in the Republican coalition is widely recognised, the full range of effects of this position on evangelicals' climate opinions is not. To move research on evangelicals from the margins of climate change opinion research, we review and integrate the interdisciplinary literature on US evangelicals, climate change, and politics. In assessing this literature, we identify three areas in need of further research. First, there is a critical need for more research on the climate attitudes of evangelicals of color, who comprise a growing share of the evangelical tradition in the US. Second, highlighting the Christian Right's active engagement in the climate debate, we identify a need for more experimental work examining how cues from religious elites may shape evangelicals' opinions. Finally, we suggest that to better harness insights across disciplines, researchers must become more explicitly aware of how different disciplines conceptualize temporality. Attending to temporal scale suggests that a new approach is needed to test how dominion beliefs, which are widely thought to be an important theological driver of climate skepticism, operate. We also suggest that two factors that appear to play a weak or limited role in driving climate skepticism over the short term (anti‐science attitudes and evangelical religiosity) may in fact play a significant role in driving skepticism over the medium term. This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Perceptions of Climate Change Trans‐Disciplinary Perspectives > Humanities and the Creative Arts Abstract : Differences between white evangelicals and evangelicals of color over the past decade highlight the need for more research on how race shapes US evangelicals' climate attitudes. Our interdisciplinary review also suggests that researchers have underestimated how evangelical religiosity shapes climate attitudes by focusing on the short term.